Occupational therapy for stroke survivors in UK care homes - Fletcher-Smith, Joanna C. (2015)
Stroke is a major contributor to the global burden of disease. It is the third main cause of death and the largest cause of adult disability in the UK. Stroke is reported to be the second most common cause of disability after dementia in the UK care home population with an estimated 25% of residents living with the consequences of stroke.